Maqāsīd al-Sharīa in the Fatwa of the Indonesian Ulama Council Regarding Congregational Worship During the COVID-19 Pandemic - Nurhayati Nurhayati; Muhammad Syukri Albani Nasution (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2020)
Abstract: The implementation of worship in the time of the COVID-19 pandemic, especially congregational worship, has led to a debatable problem among Muslims, including Muslims in Indonesia. Various Islamic groups in Indonesia share different opinions and views on the practice of worship during the pandemic. On the one hand, some groups reinforce that the COVID-19 pandemic should not become a barrier or hinder the religious practices. On the other hand, some others insisted that the practice of worship during the COVID-19 period must comply with predetermined health protocols. If necessary, it must be temporarily stopped to avoid the spread of the COVID-19 cases. In this regard, the Indonesian Ulama Council (MUI) issued fatwa number 14/2020 concerning the implementation of worship in the COVID-19 outbreak situation. This article examines and explores the basis and considerations of the MUI in establishing a fatwa regarding the implementation of worship during the COVID-19 pandemic. Using qualitative analysis methods and the theory of maqāsīd al-sharīa, this research concludes that restrictions on the implementation of worship during the pandemic - or even prohibiting the practice of congregational worship for prone areas COVID-19 transmission - are based on considerations of benefit,. which is the essence of maqāsīd al-sharīa. The aim is to ensure five primary things (faith, soul, mind, offspring, and wealth). Hence, anything that can interfere with or threaten the existence of these five things must be avoided. Abstrak: Pelaksanaan ibadah di era pandemi COVID-19, khususnya ibadah yang dilakukan secara berjamaah, telah menjadi persoalan tersendiri di kalangan umat Islam, dan tidak terkecuali untuk umat Islam di Indonesia. Berbagai kalangan memiliki pendapat dan pandangan yang berbeda-beda. Sebagian mereka berpandangan bahwa pandemi COVID-19 tidak boleh menjadi penghalang atau menghalangi pelaksanaan ibadah. Pada sisi lain, tidak sedikit juga yang berpandangan bahwa pelaksanaan ibadah di masa COVID-19 harus diatur sedemikian rupa dan jika perlu dihentikan sementara untuk menghindari semakin merebaknya kasus COVID-19. Berkenaan dengan hal tersebut, Majelis Ulama Indonesia (MUI) mengeluarkan Fatwa Nomor 14/2020 tentang Penyelenggaraan Ibadah dalam Situasi Wabah COVID-19. Artikel ini mengkaji dan mengeksplorasi dasar dan pertimbangan MUI dalam menetapkan fatwa tentang penyelenggaraan ibadah di masa pandemi COVID-19 tersebut. Dengan menggunakan metode analisis kualitatif dan teori maqāsīd al-sharīa penelitian ini menyimpulkan bahwa pembatasan pelaksanaan ibadah di masa pandemi—atau bahkan pelarangan pelaksanaan ibadah secara berjamaah untuk daerah-daerah yang yang memiliki potensi tinggi dalam penularan COVID-19—didasarkan pada pertimbangan kemaslahatan yang merupakan inti dari maqāsīd al-sharīa. Tujuannya adalah menjamin perlindungan lima hal primer (agama, akal, jiwa, keturunan dan harta). Segala sesuatu yang potensial menganggu atau mengancam eksistensi kelima hal tersebut harus dihindari.